Simple measures of ozone depletion in the polar stratosphere - Müller, R.; Grooß, J.-U.; Lemmen, C.; Heinze, D.; Dameris, M.; Bodeker, G. (HAL CCSD, 2007)
International audience We investigate the extent to which commonly considered quantities, based on total column ozone observations and simulations, are applicable as measures of ozone loss in the polar vortices. Such quantities have been used frequently in ozone assessments by the World Meteorological Organization (WMO) and to assess the performance of chemistry-climate models. The most commonly considered quantity is monthly mean column ozone poleward of a latitude of 63° in spring. For the Arctic, these monthly means were found to be insensitive to the exact choice of the latitude threshold, unlike the Antarctic where greater sensitivity was found. Choosing a threshold based on the location of the transport barrier at the vortex boundary instead of geometric latitude led to a roughly similar year-to-year variability of the monthly means, but in particular years deviations of several tens of Dobson units occurred. Moreover, the minimum of daily total ozone minima poleward of a particular latitude, another popular measure, is debatable, insofar as it relies on one single measurement or model grid point. For Arctic conditions, this minimum value occurred often in air outside polar vortex, both in the observations and in a chemistry-climate model. As a result, we recommend that the minimum of daily minima no longer be used when comparing polar ozone loss in observations and models. As a possible alternative, we suggest considering the minimum of daily average total ozone poleward of a particular equivalent latitude (or in the vortex) in spring. This definition both obviates relying on one single data point and reduces the impact of year-to-year variability in the Arctic vortex breakup on ozone loss measures. However, compact relations of such simple measures with meteorological quantities that describe the potential for polar heterogeneous chlorine activation and thus ozone loss were not found. Therefore, we argue that where possible, more sophisticated measures of chemical polar ozone loss that include ...